2016 IEEE 24th International Requirements Engineering Conference (RE) 2016
DOI: 10.1109/re.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Simulation of Legal Requirements: Experience from Tax Policy Simulation

Abstract: Abstract-Using models for expressing legal requirements is now commonplace in Requirements Engineering. Models of legal requirements, on the one hand, facilitate communication between software engineers and legal experts, and on the other hand, provide a basis for systematic and automated analysis. The most prevalent application of legal requirements models is for checking the compliance of software systems with laws and regulations. In this experience paper, we explore a complementary application of legal req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The literals in O and U are derived as follows: We compare in a pairwise manner the relative frequencies of the actual characteristics of S against the desired characteristics in H desired (L. [13][14][15]. To illustrate, consider rows 2 and 3 of Table I.…”
Section: B Generating Valid and Representative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The literals in O and U are derived as follows: We compare in a pairwise manner the relative frequencies of the actual characteristics of S against the desired characteristics in H desired (L. [13][14][15]. To illustrate, consider rows 2 and 3 of Table I.…”
Section: B Generating Valid and Representative Datamentioning
confidence: 99%
“…Although motivated by microeconomic simulation [13] rather than software testing, our previous approach provides a useful basis for generating data that can be used for statistical testing. However, the approach suffers from an important limitation: while the approach generates synthetic data that is aligned with a desired set of statistical distributions and has shown to be good enough for running financial simulations [14], the approach cannot guarantee the satisfaction of logical constraints that need to be enforced over the generated data.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the processing of usability, stakeholder and legislation requirements together is rarely systematized, and it greatly differs from one approach to another. Most of existing approaches consider stakeholders, legislation and usability as a source or nonfunctional requirements, and they are commonly catalogued and barely discerned for a proper and joint analysis [8][9][10][11][12][13][14]. In fact, the correct handling of non-functional requirements can be identified as one of the most important areas of research [8].…”
Section: Related Workmentioning
confidence: 99%
“…However, this approach is mainly focused on the architectural design, lacking of a concrete requirements engineering process. Other approaches make use of models for representing legal requirements in a specific context [14]. However, while reporting important added value by enabling simulation, stakeholder and legislation requirements should be analyzed together, in order to identify conflicts of interests in a broader context, such as in e-Government applications.…”
Section: Related Workmentioning
confidence: 99%
“…They identified that most methodologies do not provide mechanisms to articulate effectively the (potential) unwritten rules that might influence legal reasoning, such as the context of the legal scenario. Finally, Soltana et al [23] explored the potential usage of legal requirements models in simulated scenarios, such as taxation.…”
Section: Related Workmentioning
confidence: 99%